Effects of external wind breakers of Heller dry cooling system in power plants. (25th January 2018) - Seifi, Ali Reza; Akbari, Omid Ali; Alrashed, Abdullah A.A.A.; Afshary, Fazel; Shabani, Gholamreza Ahmadi Sheikh; Seifi, Reza; Goodarzi, Marjan; Pourfattah, Farzad
Graphical abstract: Schematic of symmetrical cooling tower with four wind breakers. Highlights: Dual and quadruple external wind breakers next to the cooling tower were studied. Effects of wind velocity, number and place of wind brokers were investigated. Using wind breakers, the heat loss retrieves, but maximun for quadruple wind breaker. Condenser vacuum has a direct relation with the outlet water temperature of cooling tower. Using wind breakers, outlet water temperature variation of cooling tower reduces. Abstract: The dry cooling towers (HELLER) are one of the most current cooling towers used in steam power plants. These cooling towers are mostly used in dry areas. The environmental effects are one of the important problems on the performance of these kinds of cooling towers and the most challenging problem is the velocity of wind blow inside and around the cooling tower. In present research, finite volume method and k-ε model have been used for 3-D modeling. In this study, the dual and quadruple external breakers next to the cooling tower in different wind blow velocities have been examined. By using wind breakers, the heat loss retrieves. However, this enhancement is more for quadruple wind breaker, compared to the dual wind breaker. Condenser vacuum has a direct relation with the outlet water temperature of cooling tower. By using wind breakers, outlet water temperature increment of cooling tower reduces.